2022
DOI: 10.1155/2022/2579692
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation Analysis and Intervention Study on Disturbance of Lipid Metabolism and Diabetic Peripheral Neuropathy

Abstract: Objective. To explore the significance and clinical value of dynamic monitoring of lipid metabolism indexes in patients with diabetic peridiabetic lesions. Methods. A total of 192 patients with type 2 diabetes (T2DM) treated in our hospital from October 2019 to July 2021 were divided into two groups according to whether they were complicated with peripheral neuropathy (DPN). The patients in the observation group were randomly assigned into group A ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Lastly, diabetic mice had significantly lower cholesterol metabolism than non-diabetic mice (Supplementary Table 3 ). Previous studies have shown that DM impairs cholesterol metabolism 31 , 32 , accumulating long-chain fatty acids in nerve cell membranes that interfere with their function 33 , implying that diabetic patients are more likely to develop DPN. Tavakoli et al also demonstrated the pathophysiological link between elevated triglyceride levels and corneal nerve damage 34 , suggesting the importance of regulating cholesterol metabolism to improve DCN prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, diabetic mice had significantly lower cholesterol metabolism than non-diabetic mice (Supplementary Table 3 ). Previous studies have shown that DM impairs cholesterol metabolism 31 , 32 , accumulating long-chain fatty acids in nerve cell membranes that interfere with their function 33 , implying that diabetic patients are more likely to develop DPN. Tavakoli et al also demonstrated the pathophysiological link between elevated triglyceride levels and corneal nerve damage 34 , suggesting the importance of regulating cholesterol metabolism to improve DCN prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%